Effects of Wet and Dry Intermittent Fasting on Weight and Cardiovascular Risk Indicators (Bioresearch Communications, 2021)
Intermittent fasting (IF) has two broad types: wet (with water) and dry (without water) fasting. Studies suggest that both are effective for reducing weight and for promoting overall metabolic well-being; however, their relative efficacy is not yet established. The study was a 9-day cross-over clinical trial with the purpose to compare the effectiveness of wet and dry fasting. Adult overweight women (n = 18) from Dhaka, Bangladesh were recruited as subjects of this study. It included 3 days of wet IF and 3 days of dry IF (14 h fasting and 50% calorie restriction), with a 3-day washout period (ad libitum intake) in between. Both types of IF resulted in significant weight loss. The loss was significantly higher after 3 days of dry IF (−0.23 ± 0.02 kg; P < 0.05). Waist circumference and BMI were significantly reduced in both interventions (P